Will wearable sweat lactate sensors be the next big thing in cycling? - Van Hoovels, K.; Boone, J.; Cuartero, M.; Crespo, G. A. (Journal of Science and Cycling, 2023)
The use of wearable sensors in cycling is rising. Besides heart rate, we can now measure more and more variables continuously and in real-time like glucose (in interstitial fluid), core body temperature (at the heart rate belt), muscle oxygenation (with NIRS at the upper leg), and sweat rate (with wearable sensors). These sensors may provide more insights into what is happening during exercise and possible can be used to optimize performance.